A novel regulatory function for miR‐29a in keloid fibrogenesis. (1st June 2016) - Zhang, G.‐Y.; Wu, L.‐C.; Liao, T.; Chen, G.‐C.; Chen, Y.‐H.; Zhao, Y.‐X.; Chen, S.‐Y.; Wang, A.‐Y.; Lin, K.; Lin, D.‐M.; Yang, J.‐Q.; Gao, W.‐Y.; et al.
Summary: Background: A growing body of evidence has shown that microRNA‐29 (miR‐29) plays a central role in the progression of fibrosis. However, the mechanisms underlying the role of miR‐29 in keloid fibrogenesis remain unknown. Aim: To investigate the roles of miR‐29 in dermal fibroblasts in the pathogenesis of keloids. Methods: Primary fibroblasts from 9 patients with keloid and 6 healthy controls (HCs) were cultured and pretreated with transforming growth factor (TGF)‐β1. Next, fibroblasts were transfected with precursor miRNA and anti‐miR‐29a miRNA. TGF‐β1‐associated miR‐29 alterations were investigated by quantitative real‐time PCR. Collagen I and collagen III protein levels were analysed by western blotting. Results: miR‐29a, miR‐29b and miR‐29c levels were significantly lower in keloid compared with healthy fibroblasts ( P < 0.05), and in particular, miR‐29a was especially markedly reduced ( P < 0.001). Type I and type III collagen mRNA and protein levels were decreased in keloid fibroblasts transfected with pre‐miR‐29a ( P < 0.05), whereas knockdown with anti‐miR‐29a increased type I and type III collagen mRNA and protein expression ( P < 0.05) in the fibroblasts. Interestingly, pretreatment of fibroblasts with TGF‐β1 significantly decreased miR‐29a ( P < 0.05), whereas miR‐29b and miR‐29c were reduced to a lesser extent, which was not significant. Conclusions: These findings show that miR‐29a exerts as a novel regulator in the fibrogenesis of keloid, suggesting that miR‐29a might be a novel marker for keloid.